2011
DOI: 10.1007/s12600-011-0188-y
|View full text |Cite
|
Sign up to set email alerts
|

Plant defense activation and management of tomato root rot by a chitin-fortified Trichoderma/Hypocrea formulation

Abstract: Tomato root rot caused by Rhizoctonia solani is a major soilborne disease resulting in significant yield loss. The culture filtrates of six isolates of Trichoderma/Hypocrea species were evaluated for in vitro production of hydrolytic enzymes. Results demonstrated that all the six isolates were able to produce chitinase, β-1, 3 glucanase and protease in the range of 76-235 μmol GlcNAc min -1 mg -1 protein, 31.90-37.72 nmol glucose min -1 mg -1 proteins and 63.05-86.22 μmol min -1 mg -1 proteins, respectively. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
37
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
3

Relationship

5
3

Authors

Journals

citations
Cited by 58 publications
(43 citation statements)
references
References 35 publications
3
37
0
1
Order By: Relevance
“…Several species of Trichoderma have been used as biological control agents to manage diseases of vegetable and other crops (Solanki et al 2011; Srivastava et al 2012; Al-Sadi et al 2015). In the present study, twenty isolates of Trichoderma collected from rhizosphere soil of tomato were phenotypically, biochemically and genetically characterized to identify and screen the most efficient antagonistic against four tomato fungal pathogens (FOL, AA, CG and RS).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several species of Trichoderma have been used as biological control agents to manage diseases of vegetable and other crops (Solanki et al 2011; Srivastava et al 2012; Al-Sadi et al 2015). In the present study, twenty isolates of Trichoderma collected from rhizosphere soil of tomato were phenotypically, biochemically and genetically characterized to identify and screen the most efficient antagonistic against four tomato fungal pathogens (FOL, AA, CG and RS).…”
Section: Discussionmentioning
confidence: 99%
“…They reported that the mycoparasitic capacity of various species and isolates of Trichoderma differs. There are several mechanisms involved in Trichoderma antagonism, namely, antibiosis whereby the antagonist fungus produces antibiotics, competes for nutrients and mycoparasitism, whereas Trichoderma directly attacks the plant pathogen by excreting lytic enzymes such as chitinases and β-1,3 glucanases (Kubicek et al 2001; Radjacommare et al 2010; Solanki et al 2011). Such hydrolytic enzymes partially degrade the pathogen cell wall that leads to parasitization (Howell 2003).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Trichoderma asperellum has shown biocontrol potential against Fusarium head blight by using liquid media of differing composition (Kolombet et al, 2008). A chitin fortified bioformulation of Trichoderma/Hypocrea species allowed increased accumulation of total phenols, peroxidase, polyphenoloxidase and phenylalanine ammonia lyase in treated tomato plants when challenged with R. solani (Solanki et al, 2011). The biomass paste formulation remained viable for at least 6 months at room temperature (Kolombet et al, 2008).…”
Section: Enhancement Of Shelf Life and Application Efficiencymentioning
confidence: 99%
“…The chitinolytic enzymes of microbial origins, especially exo-chitinases of Trichoderma spp. can restrict the growth of soil-borne pathogens through hydrolysis of cell wall associated chitin [3]. Chitinase production by T. harzianum was found to be induced using wheat bran-based solid medium containing 1% colloidal chitin and the chitinase lead to the lysis of the phytopathogenic fungus Colletotrichum gloeosporioides [4].…”
Section: Introductionmentioning
confidence: 99%